Comparison of Teaching Content on Inequalities between China and Indonesia - Xuezhi , Zhao; Rais, Damar (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
In this study, we select inequality content from a set of Indonesian instructional materials and compare it with the corresponding inequality content in the People’s Education Press (PEP) textbooks. The comparison is significant because the two education systems represent distinct pedagogical approaches that differ historically, culturally, and epistemologically. Moreover, they are grounded in contrasting educational philosophies. PEP follows a Chinese tradition emphasizing formal structure, systematic practice, and deductive reasoning that moves from worked examples to general rules. In contrast, the Indonesian Kurikulum Merdeka is rooted in Freudenthal’s Realistic Mathematics Education (RME), which encourages contextual modeling and meaning-making prior to the introduction of formal symbols. By comparing the topic of inequalities—an abstract concept with specific operational rules (such as reversing the inequality sign when multiplied by a negative number)—we can observe how these approaches lead to different learning experiences. Do students discover rules through structured exploration, or are they expected to apply rules within real-world contexts after the concepts are presumed to be understood? In Indonesia, inequalities are taught primarily in Grade 11 of senior high school, under the assumption that students already possess a mature level of abstract reasoning. In China, however, inequality-related content is distributed across multiple stages of elementary and secondary schooling. Both countries have undergone substantial curriculum reforms aimed at improving mathematical proficiency and educational equity, yet their textbooks continue to reflect distinct pedagogical philosophies and cultural priorities. By examining the differences across these dimensions, we hope to provide useful insights for the teaching of inequality-related content